LymphoAtlas: a dynamic and integrated phosphoproteomic resource of TCR signaling in primary T cells reveals ITSN2 as a regulator of effector functions - Marie Locard‐Paulet; Guillaume Voisinne; Carine Froment; Marisa Goncalves Menoita; Youcef Ounoughene; Laura Girard; Claude Gregoire; Daiki Mori; Manuel Martinez; Hervé Luche; Jerôme Garin; Marie Malissen; et al. (Molecular Systems Biology)
Abstract T‐cell receptor (TCR) ligation‐mediated protein phosphorylation regulates the activation, cellular responses, and fates of T cells. Here, we used time‐resolved high‐resolution phosphoproteomics to identify, quantify, and characterize the phosphorylation dynamics of thousands of phosphorylation sites in primary T cells during the first 10 min after TCR stimulation. Bioinformatic analysis of the data revealed a coherent orchestration of biological processes underlying T‐cell activation. In particular, functional modules associated with cytoskeletal remodeling, transcription, translation, and metabolic processes were mobilized within seconds after TCR engagement. Among proteins whose phosphorylation was regulated by TCR stimulation, we demonstrated, using a fast‐track gene inactivation approach in primary lymphocytes, that the ITSN2 adaptor protein regulated T‐cell effector functions. This resource, called LymphoAtlas, represents an integrated pipeline to further decipher the organization of the signaling network encoding T‐cell activation. LymphoAtlas is accessible to the community at: https://bmm-lab.github.io/LymphoAtlas .